Inflation Expectations and Misallocation of Resources - Ropele, Tiziano,Gorodnichenko, Yuriy,Coibion, Olivier (National Bureau of Economic Research, 2023)
Using Italian data that includes both inflation forecasts of firms and external information on their balance sheets, we study the causal effect of changes in the dispersion of beliefs about future inflation on the misallocation of resources. We find that as disagreement increases, so does misallocation. In times of low inflation, the aggregate TFP loss of the dispersed expectations-induced misallocation is low, but we argue that it likely becomes quite significant in times of high inflation
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Inflationserwartung; Wirkungsanalyse; Allokation; Verhaltensökonomik; Italien; Prices; Business Fluctuations; and Cycles; Monetary Policy; Central Banking; and the Supply of Money and Credit; Macro-Based Behavioral Economics